Rationalist and Reductionist: Andrew Fuller’s Response to Robert Robinson in Six Letters - Rindels, Ryan (Perichoresis, 2023)
Apologetic engagement was part and parcel of the ministry of Andrew Fuller. His most common opponents embraced extreme forms of rationalism that could not be reconciled with orthodox Calvinistic theology. Socinianism, with its denial of the deity of Christ and the doctrine of the Trinity, posed a threat to Particular Baptist churches. Fellow Baptist pastor Robert Robinson was a Socinian sympathizer, influenced by a rationalism that stripped his theology of mystery, tension, and nuance. In six letters to Robinson, Andrew Fuller addresses various topics drawn from Robinson’s writings and ministry that pertain to human nature, ethics, and hermeneutics from a confessional perspective in an Enlightenment context.